Cervical spine anomalies in Menkes disease: a radiologic finding potentially confused with child abuse - Hill, Suvimol C. (2012)
BACKGROUND: Menkes disease is an X-linked recessive disorder of copper transport caused by mutations in ATP7A, a copper-transporting ATPase. Certain radiologic findings reported in this condition overlap with those caused by child abuse. However, cervical spine defects simulating cervical spine fracture, a known result of nonaccidental pediatric trauma, have not been reported previously in this illness. OBJECTIVE: To assess the frequency of cervical spine anomalies in Menkes disease after discovery of an apparent C2 posterior arch defect in a child participating in a clinical trial. MATERIALS AND METHODS: We examined cervical spine radiographs obtained in 35 children with Menkes disease enrolled in a clinical trial at the National Institutes of Health Clinical Center. RESULTS: Four of the 35 children with Menkes disease had apparent C2 posterior arch defects consistent with spondylolysis or incomplete/delayed ossification. CONCLUSION: Defects in C2 were found in 11% of infants and young children with Menkes disease. Discovery of cervical spine defects expands the spectrum of radiologic findings associated with this condition. As with other skeletal abnormalities, this feature simulates nonaccidental trauma. In the context of Menkes disease, suspicions of child abuse should be considered cautiously and tempered by these findings to avoid unwarranted accusations.